A fluorescent probe to simultaneously detect both O-GlcNAcase and phosphatase - Boo, Jihyeon; Lee, Jongwon; Kim, Young-Hyun; Lee, Chang-Hee; Ku, Bonsu; Shin, Injae (Frontiers in Chemistry, 2023)
O-GlcNAc modification of proteins often has crosstalk with protein phosphorylation. These posttranslational modifications are highly dynamic events that modulate a wide range of cellular processes. Owing to the physiological and pathological significance of protein O-GlcNAcylation and phosphorylation, we designed the fluorescent probe, beta-GlcNAc-CM-Rhod-P, to differentially detect activities of O-GlcNAcase (OGA) and phosphatase, enzymes that are responsible for these modifications. Beta-GlcNAc-CM-Rhod-P was comprised of a beta-GlcNAc-conjugated coumarin (beta-GlcNAc-CM) acting as an OGA substrate, a phosphorylated rhodol (Rhod-P) as a phosphatase substrate and a piperazine bridge. Because the emission wavelength maxima of CM and Rhod liberated from the probe are greatly different (100 nm), spectral interference is avoided. The results of this study revealed that treatment of GlcNAc-CM-Rhod-P with OGA promotes formation of the GlcNAc-cleaved probe, CM-Rhod-P, and a consequent increase in the intensity of fluorescence associated with free CM. Also, it was found that exposure of the probe to phosphatase produces a dephosphorylated probe, Beta-GlcNAc-CM-Rhod, which displays strong fluorescence arising from free Rhod. On the other hand, when incubated with both OGA and phosphatase, beta-GlcNAc-CM-Rhod-P was converted to CM-Rhod which lacked both beta-GlcNAc and phosphoryl groups, in conjunction with increases in the intensities of fluorescence arising from both free CM and Rhod. This probe was employed to detect activities of OGA and phosphatase in cell lysates and to fluorescently image both enzymes in cells. Collectively, the findings indicate that beta-GlcNAc-CM-Rhod-P can be utilized as a chemical tool to simultaneously determine activities of OGA and phosphatase.